2000
DOI: 10.1002/(sici)1099-1573(200002)14:1<20::aid-ptr542>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peppermint oil and caraway oil on gastroduodenal motility

Abstract: The effect of enteric‐coated (Enteroplant®) and non‐enteric‐coated preparations containing a peppermint–caraway oil combination with 90 mg peppermint oil and 50 mg caraway oil was studied on gastroduodenal motility with stationary manometry in six healthy volunteers. The results showed that: (1) both enteric‐coated and non‐enteric‐coated preparations have effects on the migrating motor complex (MMC); (2) mainly a decrease in the number of contractions and contraction amplitudes is seen during the various phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 12 publications
3
70
0
2
Order By: Relevance
“…In physiological testing, ginger increases fasting antral contractions and the gastric motor response to eating (Micklefield et al, 1999). Furthermore, ginger reverses cisplatin-induced delays in gastric emptying in animal models (Sharma and Gupta, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In physiological testing, ginger increases fasting antral contractions and the gastric motor response to eating (Micklefield et al, 1999). Furthermore, ginger reverses cisplatin-induced delays in gastric emptying in animal models (Sharma and Gupta, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Peppermint oil and menthol are carminative and gastric sedative, which relax gastrointestinal muscle both in vitro and in vivo [16,17,18,19]. Using a receptor binding assay, Hawthorn et al [20] demonstrated competitive antagonism with L-menthol of [ 3 H]-nitrendipine and the dihydropyridine radioligand [ 3 H]-(+)-PN200-110 binding to cardiac, neuronal and intestinal smooth muscle.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, PO is a well -known, harmless substance that inhibits GI smooth muscle contractility 15) . As its major constituent is menthol, PO relaxes GI smooth muscle tissues by reducing the influx of calcium into the muscle cells 16) .…”
Section: Ofmentioning
confidence: 99%